Collaborative management of forests - Wollenberg, Eva Karoline; Campbell, Bruce M.; Shackleton, S.; Edmunds, D.; Shanley, P. (International Food Policy Research Institute, 2004)
Governments around the world increasingly seek to manage their forests with the collaboration of the people living nearby. Ministries of forestry or their equivalents usually do this by offering local people access to selected forest products or forest land, income from forest resources, or opportunities for communicating with government forestry officials. In return, the agency obliges local people to cooperate in managing the forests around them by protecting existing forest or by planting trees. Governments claim that the programs devolve control over forests to local people and provide more secure livelihoods, as well as help maintain and regenerate forests. By sharing rights among local groups and the state, the programs also help to reconcile the resource claims of local people with those of the national government. Everybody supposedly wins. Millions of the rural poor now participate in collaborative forest management schemes under a variety of tenurial and organizational arrangements.We examine those arrangements and ask whether local people have indeed gained more access to benefits from and control over forests. Our findings suggest that most co-management projects actually maintain and even extend central government control.Where communities had already managed forests in Orissa and Uttarakhand in India, the government required that they share their incomes with the state forest department. Governments in many countries typically predetermine which species can be planted in reforestation or agroforestry schemes and what types of organizations can be given rights to manage forests.Whereas local people have gained greater legal access to forests and some might have increased their incomes, many have also lost out. For example, game areas and plantations have been frequently established on land used by poorer members of communities for grazing or cultivation. Local people have also not shown a consistent interest in forest management.